2019
DOI: 10.3389/fnbeh.2019.00068
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Bed Nucleus of the Stria Terminalis in PTSD: Insights From Preclinical Models

Abstract: Post-traumatic stress disorder (PTSD) afflicts approximately 8% of the United States population and represents a significant public health burden, but the underlying neural mechanisms of this and other anxiety- and stressor-related disorders are largely unknown. Within the last few decades, several preclinical models of PSTD have been developed to help elucidate the mechanisms underlying dysregulated fear states. One brain area that has emerged as a critical mediator of stress-related behavioral processing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 187 publications
(246 reference statements)
1
28
0
Order By: Relevance
“…Furthermore, lesioning this area reduces inappropriate fear to a non-reinforced CS in rats with high-trait anxiety ( Duvarci et al, 2009 ). Indeed, a growing number of lesion and functional neuroimaging studies in non-human primates and humans have implicated the BNST in the processing of uncertain threat (see Goode et al, 2019 ; Miles and Maren, 2019 ). Together, these findings suggest that inhibitory properties of the partially reinforced CS could be signaled by the IL downstream to the BNST, thereby limiting the expression of CS-induced fear to a level appropriate to its partial reinforcement history.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lesioning this area reduces inappropriate fear to a non-reinforced CS in rats with high-trait anxiety ( Duvarci et al, 2009 ). Indeed, a growing number of lesion and functional neuroimaging studies in non-human primates and humans have implicated the BNST in the processing of uncertain threat (see Goode et al, 2019 ; Miles and Maren, 2019 ). Together, these findings suggest that inhibitory properties of the partially reinforced CS could be signaled by the IL downstream to the BNST, thereby limiting the expression of CS-induced fear to a level appropriate to its partial reinforcement history.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both rodent and primate research has identified brain regions, such as the bed nucleus of the stria terminalis (BNST), amygdala, prefrontal cortex, cingulate cortex, and hippocampus, that regulate stress-related behavioral mechanisms and are dysfunctional in PTSD patients 146 . The BNST, in particular, has been investigated for its role in fear memory neural circuitry 221 . In mice, optogenetic photoinhibition of neurons projecting between the BNST and ventral tegmental area during electric shock stress decreased freezing in the exposure context and closed arm entries in the EPM 222 .…”
Section: Cross-species Comparisonsmentioning
confidence: 99%
“…The bed nucleus of the stria terminalis (BNST) is a limbic forebrain structure activated during aversive situations that has been implicated in physiological and behavioral responses to stress (Crestani et al, 2013; Miles and Maren, 2019; Myers, 2017; Radley and Johnson, 2018). Regarding stress-evoked cardiovascular responses, previous studies have indicated that the control of stress-evoked cardiovascular adjustments by the BNST seem to depend on the type of stress (Crestani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%